2016
DOI: 10.1002/ange.201608165
|View full text |Cite
|
Sign up to set email alerts
|

Selective Production of Carbon Monoxide via Methane Oxychlorination over Vanadyl Pyrophosphate

Abstract: Acatalytic process is demonstrated for the selective conversion of methane into carbon monoxide via oxychlorination chemistry.T he process involves addition of HCl to aC H 4 -O 2 feed to facilitate CÀHb ond activation under mild conditions,leading to the formation of chloromethanes,CH 3 Cl and CH 2 Cl 2 .T he latter are oxidized in situ over the same catalyst, yielding CO and recycling HCl. Amaterial exhibiting chlorine evolution by HCl oxidation, high activity to oxidize chloromethanes into CO,a nd no ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The selectivity of CO was higher over VOPO 4 , similar to the observation for the oxychlorination of CH 4 over this catalyst. 40 We also examined the catalytic performances of rare earth metal oxides, which were stable for the oxychlorination of CH 4 . 36 Among the rare earth metal oxides examined, CeO 2 demonstrated the highest C 3 H 6 yield in the conversion of C 3 H 8 .…”
Section: Catalytic Behaviors Of Metal Oxides For Conversion Of C 3 H ...mentioning
confidence: 76%
See 1 more Smart Citation
“…The selectivity of CO was higher over VOPO 4 , similar to the observation for the oxychlorination of CH 4 over this catalyst. 40 We also examined the catalytic performances of rare earth metal oxides, which were stable for the oxychlorination of CH 4 . 36 Among the rare earth metal oxides examined, CeO 2 demonstrated the highest C 3 H 6 yield in the conversion of C 3 H 8 .…”
Section: Catalytic Behaviors Of Metal Oxides For Conversion Of C 3 H ...mentioning
confidence: 76%
“…CeO 2 36 and LaOCl 38,39 catalyzed the oxychlorination of CH 4 to CH 3 Cl, whereas CO was selectively formed during the oxychlorination of CH 4 over (VO) 2 P 2 O 7 catalyst. 40 Many factors may control the product selectivity in the oxychlorination and oxybromination of CH 4 over different types of catalysts. 41 Although many studies have been devoted to the oxidative halogenation of CH 4 , only a few papers have focused on the conversion of C 2 H 6 or C 3 H 8 by this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial application of this oxyhalogenation reaction has not been considered to date because of the low CO selectivity (<50%). 166,170 Ramirez et al 171 demonstrated the first example of a highly selective one-step CO production from methane via oxychlorination chemistry. In the process, HCl was added to a CH 4 −O 2 to activate the C−H bond under mild reaction conditions while forming CH 3 Cl, CH 2 Cl 2 , and chloromethanes.…”
Section: Methane Conversionmentioning
confidence: 99%
“…The high selectivity toward CH 3 Br was attributed to the high activity of the catalyst for HBr oxidation and low activity toward the oxidation of methane and the methyl halide. In more recent work, Pérez-Ramírez et al demonstrated the one-step production of CO from methane by selective oxychlorination, yields of up to 35% at 96% selectivity of CO were obtained over stable VPO catalyst at mild reaction conditions[163]. The process involved an approach combining C-H bond activation in the presence of HCl and O 2 yielding CH 3 Cl and CH 2 Cl 2 , followed by the in-situ oxidation of halogenated products to CO and the regeneration of HCl over the VPO catalyst.…”
mentioning
confidence: 99%